SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SANTRI TELADAN PONDOK PESANTREN AL MUNAWWIR KOMPLEK NURUSSALAM DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) BERBASIS PHP - Yuli Praptomo PHS; Moh Sidik Warsono (LPPM STMIK El Rahma Yogyakarta, 2019)
Al Munawwir Islamic Boarding School, Nurussalam Complex, is still considered a non- modern cottage, all types of calculation, inputting, analysis can still be said to have not been a computerized system. So to realize a modern boarding school there must be a system that can change the work to be more practical, easy, fast and correct. The Al Munawwir Islamic Boarding School Nurussalam Complex holds an Exemplary Santri Election every year. Because the existence of a model student santri election was made to produce inaccurate data, because all data retrieved was not based on a correct data. The results of the research conducted is the application program for the Santri Decision Support System modeled by the AHP Method. This Decision Support System Application is based on PHP. The application of this Decision Support System is only for helpers to make more accurate and accurate model student examples with data taken correctly